PERLINDUNGAN HUKUM KEPADA PEMEGANG HAK CIPTA LAGU, YANG LAGUNYA DI REMIX PADA APLIKASI TIKTOK - Aditya Reynaldi Pratama (2022)
TikTok is an application that is on the rise among young people, particularly since Covid - 19 hit the whole world. In TikTok application itself, so many users of the app are very creative in a way to expressing something through short videos with a song on the background. However, because of this many users of TikTok, was use the song without permissions and make remixed version for the background to their short videos. The act of remixing a song without permission is clearly an act that violates copyright holder. This aims to find out wheter the laws that apply in Indonesia are clearly firm for remixed song, and what mechanism should be taken for the copyright holder. All of this was done for the welfare of the creator